Assessing Maladaptive Personality in the Forensic Context: Development and Validation of the Personality Inventory for DSM-5 Forensic Faceted Brief Form (PID-5-FFBF). Issue 1 (2nd January 2022) - Niemeyer, Lisa M.; Grosz, Michael P.; Zimmermann, Johannes; Back, Mitja D.
Abstract: The current study proposes an adaptation of the PID-5 to assesses maladaptive personal traits in forensic settings. Specifically, we adapted the item set of the PID-5 Faceted Brief Form (PID-5-FBF) to the forensic context and validated the resulting PID-5 Forensic Faceted Brief Form (PID-5-FFBF) using self- and informant-reports of 199 male prisoners. Exploratory factor analyses suggested a four-factor solution comprising Antagonism, Detachment, Disinhibited Aggression, and Insecurity. Antagonism and Detachment were very similar to the domains with the same name from the five-factor solution of the PID-5. Insecurity conceptually resembled Negative Affectivity. Disinhibited Aggression represented a forensically highly relevant composition of Antagonism, Disinhibition, and Negative Affectivity. We report results for this four- and the canonical five-factor solution throughout the manuscript. The PID-5-FFBF domains showed convergent associations with the corresponding Big Five personality traits. Furthermore, the PID-5-FFBF domains were differentially correlated with indicators of psychological adjustment and forensically relevant outcomes such as institutional misbehavior and risk for reoffending. In particular, Insecurity was associated with lower levels of psychological adjustment, while Antagonism and Disinhibited Aggression were associated with higher levels of institutional misbehavior and risk for reoffending. These findings provide initial evidence for the validity and utility of the PID-5-FFBF in forensic settings.